Educomunicación, tics y prisión. Testimonios de personas privadas de libertad en torno a la exclusión digital - Ddo. José María MERCHÁN BERMEJO ,Dra. Susana DE ANDRÉS DEL CAMPO,Dr. Agustín GARCÍA MATILLA (Fonseca, Journal of Communication, 2023)
This article presents the results of a qualitative investigation on the perception of the internal people of the Topas prison, Salamanca (Spain) about the educational opportunities and the use of ICTs they carry out in prison. They value the technological gap and the lack of opportunities to compensate it as a handicap, since, in their opinion, it will stop their integration opportunities.